Online marketing : a boon or bane for businesses? - Lee, Daphne Mun Lyn (2008)
A study on the differences between online marketing and traditional marketing methods. An analysis of whether the online avenue is replacing traditional methods, and the possibility of MNCs using it solely as a marketing strategy. Future growth of online marketing and its impact on businesses will be examined.